Identification of Sedge and Sedge-Like Weeds in Florida Citrus - Stephen H. Futch; David W. Hall (EDIS)
Sedges are annual or mostly perennial grass-like plants with aerial flower-bearing stems. In annual forms, the stem is solitary to mostly several with basal leaves. Perennial forms have a thick rootstock or an erect to horizontal underground rhizome usually with shortened internodes. Sedges are of little economic value to man but can be very competitive with the desired crop for water, nutrients and space. This document is HS962, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published March 2004.